2009
DOI: 10.1128/mcb.00406-09
|View full text |Cite
|
Sign up to set email alerts
|

Selective Use of ADAM10 and ADAM17 in Activation of Notch1 Signaling

Abstract: Notch signaling requires a series of proteolytic cleavage events to release the Notch intracellular domain (NICD) that functions directly in signal transduction. The Notch receptor is locked down in a proteaseresistant state by a negative regulatory region (NRR) that protects an ADAM (a disintegrin and metalloprotease) cleavage site. Engagement with ligand-bearing cells induces global conformational movements in Notch that unfold the NRR structure to expose the ADAM cleavage site and initiate proteolytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
242
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(257 citation statements)
references
References 62 publications
12
242
0
Order By: Relevance
“…We also identified S1P-induced Notch activation without Notch ligands. Consistent with our observations, previous studies have shown that ADAM17 mediates ligand-independent Notch activation, while ADAM10 is ligand dependent 38,39 . Another study has shown that soluble form of Jagged1 activates Notch signalling without cell-cell contact 40 .…”
Section: Discussionsupporting
confidence: 82%
“…We also identified S1P-induced Notch activation without Notch ligands. Consistent with our observations, previous studies have shown that ADAM17 mediates ligand-independent Notch activation, while ADAM10 is ligand dependent 38,39 . Another study has shown that soluble form of Jagged1 activates Notch signalling without cell-cell contact 40 .…”
Section: Discussionsupporting
confidence: 82%
“…TNF-a has been reported to show an increased expression in OSCC specimens 27 and promote S2 cleavage (resulting in NICD Notch1 in oral squamous cell carcinoma R Yoshida et al production) via TACE maturation in Notch signaling. [28][29][30] As shown in Figure 5, NICD cleavages were observed in a TNF-a concentration-dependent manner. In addition, NICD cleavage was inhibited by GSI treatment.…”
Section: Tnf A-dependent Oscc Cell Invasivenessmentioning
confidence: 90%
“…Notch is a putative substrate of ADAM-10 and ADAM-17 [59] and, therefore, its possible inactivation by GM6001 may enhance neuroblast generation in the injured tissue.…”
Section: Implication Of Adam-17/tgf-a/egfr In the Creation Of A Non-nmentioning
confidence: 99%